BIOMATERIALS USED IN ORAL REHABILITATION OF THE EDENTULOUS ALLERGIC PATIENTS - Grădinaru Irina; Antohe Magda-Ecaterina; Hurjui Loredana Liliana (Romanian Society of Oral Rehabilitation, 2018)
The aim of this study was to present some practical possibilities of oral rehabilitation by using thermoplastic materials and flexible biomaterials for the removable dentures in edentulous allergic patients. . Material and Methods: The study lot included a number of 20 patients diagnosed with total and partially extended edentation showing allergies to classic acrylic prostheses, manifested at the level of the oral mucosa. They presented allergenic reactions when they were treated by removable dentures made by classic PMMA. After methodical clinical and complementary examinations, the patients received a new prosthetic treatment made by thermoplastic materialsand flexible biomaterials, according with particularities of clinical case Results: The construction of a total denture using the Polyan thermosetting material (modified methacrylate). The main feature of this material refers to the content of residual monomer, which is significantly lower than in the case of conventional dentures based on thermos-polymerizable polymethyl methacrylate. Flexible, monomer-free biomaterials are the ideal therapeutic choice in case of patients diagnosed with partially extended edentation who show allergies to classic acrylates. Conclusions: Nowadays, thermoplastic materials, due to their superior properties and their precision of manufacturing in the dental lab represent a better alternative used for removable dentures, comfortable and very well accepted by patients.